Synthesis carbonic anhydrase enzyme inhibition and antioxidant activity of novel benzothiazole derivatives incorporating glycine, methionine, alanine, and phenylalanine moieties - Deniz Üzeroğlu Payaz; F. Zehra Küçükbay; Hasan Küçükbay; Andrea Angeli; Claudiu T. Supuran (Taylor & Francis Group, 2019)
Thirteen novel benzothiazole derivatives incorporating glycine, methionine, alanine, and phenylalanine were synthesised by facile acylation reactions through benzotriazole or DCC mediated reactions and their structures were identified by 1H-NMR, 13C-NMR, and FT-IR spectroscopic techniques and elemental analysis. The carbonic anhydrase (CA, EC 4.2.1.1) inhibitory activity of the new compounds was assessed against four human (h) isoforms, hCA I, hCA II, hCA V, and hCA XIII. Some of the synthesised compounds showed good in vitro carbonic anhydrase inhibitory properties, with inhibition constants in the micromolar level. The new amino acid benzothiazole conjugates found to be more effective against hCA V and hCA II inhibition. In vitro antioxidant activities of the novel compounds were determined by DPPH method. Most of the synthesised compounds showed moderate to low antioxidant activities compared to the control antioxidant compounds (BHA and α-tocopherol).